Prehospital emergency care provider’s understanding of their responsibilities towards a mental health care user, during a behavioural emergency - Stander, Charnelle (Division of Emergency Medicine, 2020)
Background: Prehospital emergency care providers in South Africa are regularly called to assist with the management of mental healthcare users. The Mental Health Care Act no 17 of 2002 regulates mental healthcare in South Africa but makes no reference to the roles and responsibilities of prehospital emergency care providers in the provision of mental healthcare, rather giving the South African Police Services authority over the wellbeing of a mental healthcare user outside the hospital setting. Aims: To investigate what prehospital emergency care providers understand their responsibilities are towards a mental healthcare user and the community during the management of a behavioural emergency. Setting: Prehospital emergency care providers from the three main levels of care, currently operational within the boundaries of Pretoria. Methods: A grounded theory qualitative study design was chosen using semi-structured focus groups for each level of prehospital emergency care; Basic Life Support, Intermediate Life Support and Advanced Life Support. Data from each focus group was collected through audio recordings, transcribed and analysed using a framework approach. Results: A total of 19 prehospital emergency care providers from all three main levels of care participated in the focus group discussions (4 BLS, 6 ILS and 9 ALS). Four main themes were identified: Perceptions of behavioural emergencies, responsibilities, understanding of legislation and barriers experienced. Conclusion: Participants placed high value on their moral and medical responsibilities towards a mental healthcare user and would like to have the backing of legislation to fulfil their role. There is a desire for better education, skill development and awareness of mental healthcare in the prehospital emergency care setting.